(3QTO GddHjH Edi eYGTQI GdMHjHs - (3CMeO Hf eMeO Hf Ydj, CHh GdYHGS , GHf napdjnJI Gdjefj,J (B731 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GSaJGOG HPcQghHYO aEfi deG fXQJ Edi TcQ GdefYe hJcQGQ EMSGfg Ydi Gdebd hGdeYOe s
(3BNQgG (B:s
(3bO LeYJ ai gPG GdcJGH eG bOeJ ajg GdYPQ ai Ghdg CSCJ hGddg ajeG bO LeYJ dg aCSJbjd ebjd GdeSJbdjfG jGQH dGJNRfi jhe GdMSGH Hg jGbGQF GdNW bd HGddg BejfG s
(3YdjgG Jedc eDQN SfI (B903 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B223 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B20s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B41 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B904s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(563) s
Keywords: (3GdCOHs